METTL9 as a protein biomarker predicts the prognosis and immunotherapy response of skin-cutaneous melanoma - Tang, Song; Zhang, Yiran; Luo, Simin; Wang, Wendan; Wu, Xunxin; Zhao, Xiaoxu; Leng, Yin (Annals of medicine and surgery, 2025)
The role of methyltransferase-like proteins (METTLs) in skin cutaneous melanoma (SKCM) remains unclear. This study investigates the expression of METTLs, particularly METTL9, in SKCM and its clinical significance. Through multiple database analyses and immunohistochemical experiments, we found that METTL9 is significantly upregulated in SKCM tissues, and its expression level is closely associated with tumor-node-metastasis stage, N stage, and ulceration status. Patients with high METTL9 expression have a poor prognosis and show a reduced response to immunotherapy. Furthermore, METTL9 is identified as an independent risk factor for poor prognosis in SKCM patients.